The prevalence and sociodemographic characteristics correlates of depressive symptoms among schoolchildren in Cyprus: A cross‑sectional descriptive correlational study - Alexandrou, Giorgos; Karanikola, Maria; Chatzittofis, Andreas; Sokratous, Sokratis (My University, 2023)
Background and aims: Mood disorders appear for the first time in childhood, especially depression. The present study aims to: (a) explore the prevalence of depressive symptoms and related predictors in a national sample of primary school children in Cyprus and (b) investigate effect size for any significant group differences. Methods: A cross-sectional descriptive study was conducted. The data were collected from the final year students of elementary education schools, aged 11-13 years, on a nationwide random sample between 2020 -2023. Clinical depressive symptoms were reported as CDI-2 total score ≥20, regardless of gender, age, or nationality. Descriptive statistics for all socio-demographic characteristics and depressive symptoms were calculated and stated as frequencies, mean values, and standard deviation. The odds ratio and 95% confidence intervals of depressive symptoms by the sociodemographic characteristics were estimated in logistic regression models before and after controlling for potential confounders Results: The final sample consisted of 552 children. 14.3% of primary education school children in Cyprus, reported clinical symptoms of depression. Concerning the Effect Size (ES) it appeared that family income in combination with parental status had the greatest ES (n2=.047, small ES). Although, girls are 1.93 times more likely to report symptoms of clinical depression (p=.002), and children with mental health problems are also at greater risk of developing symptoms of depression (OR:5.56, p=.001). Conclusion: Our findings emphasize the importance of screening school-age children for depression in order to provide early intervention. Programs to prevent mental disorders in children may focus on vulnerable groups.
Keywords: Mood disorders; Primary school children; Cyprus